2019
DOI: 10.1038/s41598-019-54445-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic shift induced by synthetic co-cultivation promotes high yield of chain elongated acids from syngas

Abstract: Bio-catalytic processes for sustainable production of chemicals and fuels receive increased attention within the concept of circular economy. Strategies to improve these production processes include genetic engineering of bio-catalysts or process technological optimization. Alternatively, synthetic microbial co-cultures can be used to enhance production of chemicals of interest. It remains often unclear however how microbe to microbe interactions affect the overall production process and how this can be furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 25 publications
6
80
0
Order By: Relevance
“…Such interactions can be relevant for the overall fitness of microbial communities as they influence thermodynamics of the system. Diender et al (2019) have recently shown a similar synergistic relation in synthetic co-cultures of Clostridium autoethanogenum and Clostridium kluyveri. In that study, it was shown that the presence of the ethanol-consuming bacterium C. kluyveri induced a higher degree of solventogenesis by the carboxydotrophic organism (compared with monocultures of C. autoethanogenum).…”
Section: Discussionmentioning
confidence: 64%
“…Such interactions can be relevant for the overall fitness of microbial communities as they influence thermodynamics of the system. Diender et al (2019) have recently shown a similar synergistic relation in synthetic co-cultures of Clostridium autoethanogenum and Clostridium kluyveri. In that study, it was shown that the presence of the ethanol-consuming bacterium C. kluyveri induced a higher degree of solventogenesis by the carboxydotrophic organism (compared with monocultures of C. autoethanogenum).…”
Section: Discussionmentioning
confidence: 64%
“…MCFA are used to produce pharmaceutical and personal care products, animal feed additives and lubricants, among other, and can be converted chemically or enzymatically into valuable biofuel molecules such as methyl esters, methyl ketones, alkenes and alkanes [13,14]. The theoretical maximum yield of hexanoate production in a co-culture of C. autoethanogenum and C. kluyveri is 0.056 mmol of hexanoate per mmol of CO, whereas the yield obtained in the most recent study [11] was 0.009 mmol hexanoate per mmol of CO, so there is substantial room for improvement and new strategies need to be developed.…”
Section: Introductionmentioning
confidence: 94%
“…Transcriptomic data was obtained from steady-state co-cultures grown in chemostats [11]. The Genomes of C. autoethanogenum: DSM 10061 (GCA 000484505.1) [31] and C. kluyveri : DSM 555 (GCA 000016505.1) [32] were retrieved from the European Nucleotide Archive.…”
Section: Calculation Of Species Abundancesmentioning
confidence: 99%
See 2 more Smart Citations